New perspectives in the sources of the story of corporatism in Italy - Nemore, Francesca (Oficina do Historiador, 2016)
The historical reconstruction of the Italian corporatism, during the fascist period, has become intertwined and has been hampered by the story of a lost archive. The story of the archive dispersion is interesting because it is not just an archival history but weaves and holds the political and economic history of the Fascist period, but also that of the previous period and the next. The archive that we are talking about is that of the Ministry of Corporations: the main body of the Italian economy government under fascism. The subject of this work is the analysis of "fanciful" theories over the years justified the archive disappeared and the reconstruction through archive subsidiary sources same. The idea of seeking the documentation, fragmented in various locations, and then to set up a guide sources for the history of the Ministry of Corporations, was founded in 2009 by some considerations, much discussed in recent Italian historiography, on the economic policy of the fascist period and little verifiable in the absence of direct institutional sources that enable it to give a confirmation or denial to initial hypotheses, taking into account the subject of an institutional point of view the role of which (long little rated) appears very significant today. It is, in fact, reasonable to believe that there was a continuity between the policies of state intervention economy of fascism and those applied prior to the liberal governments and then in the first fifty years of Republican history, both in the administrative structures in both the strictly industrial.